Integrated lab door access control (iLDAC) - Cheng, Wei Quan (2018)
Integrated Lab Door Access Control system is a mobile application that integrated with RFID technology. The system is developed to prevent the problem of no record for check-in/out of users from lab, users forgot to bring access card, ease the users to submit request form to use lab, and reduce the time consuming on manually lock the door. The objectives of this project is to study the implementation of RFID technology in iLDAC mobile application. Besides, this project is to develop a mobile application that integrated with RFID technology in order to improve the existing system. The last objective of this project is to test the functionality and effectiveness of RFID technology in iLDAC mobile application. The system is available for Android, iOS, and Windows. However, there are some constraints when use the system on Windows. The system has 4 type of users, which are lab assistant, student, lecturer, and admin. The technology that applied in this project include Ionic Framework, TypeScript, CSS, HTML5, and Arduino. The methodology that applied in this project is Agile Software Development. This is because this methodology allow the developers to make changes and improvement even though it is late in the development cycle. This help to increase the client satisfaction since meeting with client can be done frequently. Integrated Lab Door Access Control system have several functions which are view report, generate report, submit request form, manage request, lock the door, open the door using application, and notify the users to leave the lab. This system has been tested by client using User Acceptance Test (UAT). The tested result shows that the system is working well, bug free, and meet the user requirements as stated in Software Requirement Specification.